The governance mechanism’s influence to fulfill Sharia criteria and the cash placement - Muslich Anshori, Sri Iswati, Ahmad Faisal Haq,; Edman Syarief, Moch. (Opción, 2019)
This study aims to determine the effect of corporate governance mechanisms on the fulfillment of Sharia stock criteria in companies incorporated in the ISSI as well as on the tendency of corporate cash arrangement at financial institutions via comparative quantitative research methods. The result shows that there is a significant influence on the board of directors on the placement of cash in conventional banks. In conclusion, the board of commissioners should have the same views as the representatives of the owners to place the company’s cash on a non-usury-based financial institution.